1984
DOI: 10.1007/bf01908309
|View full text |Cite
|
Sign up to set email alerts
|

Is the rat a suitable model for studying alcoholic cardiomyopathy? Hemodynamic studies at various stages of chronic alcohol ingestion

Abstract: Three groups of wistar rats with chronic alcohol consumption were studied: 10% ethanol for 6 months, 20% ethanol for 7 months, 20% ethanol for 12 months. In the intact heart in situ, left ventricular parameters of pressure, volume, and blood flow were recorded. On the average, body weight and heart weight of the alcohol-fed rats (A) were diminished by 10% as compared with controls (C). If end-diastolic volume is related to heart weight, no significant differences in the pressure-volume relations between C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Therefore, evaluation of graft function on early phase after heart transplantation has clinical significance and importance. Additionally, even though a chronic alcohol ingestion rat model can have more clinically significant scenario, it has been shown that the rat is not very suitable model for studying ''alcoholic cardiomyopathy'' [42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, evaluation of graft function on early phase after heart transplantation has clinical significance and importance. Additionally, even though a chronic alcohol ingestion rat model can have more clinically significant scenario, it has been shown that the rat is not very suitable model for studying ''alcoholic cardiomyopathy'' [42].…”
Section: Discussionmentioning
confidence: 99%